An Analysis of Midwifery Students' Mastery and Difficulties in Understanding English Medical Vocabulary at STIKES Amanah Makassar - Dien Afni Ariyati; Rostina Alimuddin; Sri Hariati Mustari; Amina Ahmad; Syarifah Masita (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
English medical vocabulary is essential for supporting midwifery students’ academic learning and future professional communication in healthcare settings. However, many students still face difficulties understanding medical terminology because of its specialized nature and limited exposure in language learning contexts. This study aimed to analyze midwifery students’ mastery and difficulties in understanding English medical vocabulary at STIKES Amanah Makassar. A descriptive qualitative design was employed involving ten second-semester Midwifery students enrolled in the English for Midwifery course. Data were collected through a vocabulary task and semi-structured interviews, then analyzed using an interactive qualitative data analysis model. The findings showed varying levels of vocabulary mastery. Five participants demonstrated good mastery, while the others showed average or limited understanding. Students generally understood common medical vocabulary but had difficulty comprehending specialized terms. The main challenges included unfamiliar terminology, pronunciation problems, difficulty remembering vocabulary, and limited exposure to English medical terms. The study concludes that vocabulary mastery is influenced by students’ familiarity with medical terminology and opportunities for contextualized learning. Therefore, integrating discipline-specific vocabulary instruction and pronunciation practice into English for Midwifery courses is necessary to improve students’ understanding and communication competence.